Effects of roasting by charcoal, electric, microwave and superheated steam methods on (non)volatile compounds in oyster cuts of roasted lamb. (February 2021) - Liu, Huan; Ma, Jianrong; Pan, Teng; Suleman, Raheel; Wang, Zhenyu; Zhang, Dequan
Abstract: This work was conducted to compare (non)volatile compounds and sensory evaluation of oyster cuts of roasted lamb. Three newer roasting methods, namely electrically heated air (EHA), microwave heat (MWH) and superheated steam (SHS), were compared with traditional burning charcoal (BCC). The results showed that the 3 new roasting methods all generated rich nonvolatile compounds and volatile compounds in samples, which was similar to the results of those prepared by BCC. Particularly, the EHA produced more nonvolatile compounds and higher equivalent umami concentrations than the other new methods, especially regarding umami amino acids. Moreover, the EHA and SHS methods had better sensory evaluations than the MWH, including acceptability, fat and roast flavours, and they had better odour activity values (OAVs) of characteristic volatile compounds, such as octanal, nonanal and ( E, E )-2, 4-decadienal. It was concluded that the EHA might be a potential method to replace the BCC due to our findings about nonvolatile compounds, OAVs of volatile compounds and sensory evaluation Highlights: 3 New roasting methods all produced rich flavour compounds in roasted oyster cuts . The EHA generated more nonvolatile compounds. The EHA and SHS formed more volatile compounds. The EHA was a great method to replace the BCC.